Methodological model for teacher innovation and evaluation (Journal of Management and Business Education, 2018)
The present paper, developed within the Educational Network for the Development and Professional Teacher Evaluation (Redepd), analyzes the synergies of the systematization of educational experiences and the Deca model with the aim of proposing a methodology for innovation and teacher evaluation. Systematization of Educational Experiences (ESS) entails construction of knowledge and favours empowerment and transformation based on the current context of the participating agents. Likewise, the Model for Development and Evaluation of Academic Competencies (M-Deca), developed within the framework of the Redeca network (Network for Development and Evaluation of Academic Skills), is a proposal to develop and evaluate competences from a critical perspective and through a process of academic reflection. Both, in the hands of teachers, become powerful tools to generate a process of reflection and critical analysis of their actions in the classroom to improve their teaching practice based on the levels of excellence and quality education required by the European Higher Education Area (EHEA).
Keywords: systematization of educational experiences; Deca model; educational reflection; teaching innovation; teacher evaluation